The Cossacks and religion in early modern Ukraine - Plokhy, Serhii, 1957- (Oxford University Press, 2001)
The author explores Cossack involvment in the religious struggles between Eastern Orthodoxy and Roman Catholicism during the early modern period. These struggles helped shape not only Ukrainian but also Russian and Polish cultural identities.